2022
DOI: 10.1038/s41598-022-23120-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impacts of land cover change on gross primary productivity globally

Abstract: Historically, humans have cleared many forests for agriculture. While this substantially reduced ecosystem carbon storage, the impacts of these land cover changes on terrestrial gross primary productivity (GPP) have not been adequately resolved yet. Here, we combine high-resolution datasets of satellite-derived GPP and environmental predictor variables to estimate the potential GPP of forests, grasslands, and croplands around the globe. With a mean GPP of 2.0 kg C m−2 yr−1 forests represent the most productive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 64 publications
3
14
0
Order By: Relevance
“…Su et al (2021) modeled yield gains under Conservation Agriculture (CA) and various practices for the future climate scenarios and found out that overall performance of CA will most likely decrease in the future in most temperate regions in South 2/24 America, including Uruguay, southern Brazil and northern Argentina for barley, cotton, rice, sorghum and sunflower. Krause et al (2022) has recently modelled the impacts of anthropogenic land cover changes on global Gross Primary Productivity (GPP) using maps of historical agricultural expansion and future land-use changes based on the 25 km resolution LUH2 dataset (Hurtt et al, 2020). Their results indicate that global GPP might get further reduced owing to agricultural expansion and to extents that depend on the prevailing scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al (2021) modeled yield gains under Conservation Agriculture (CA) and various practices for the future climate scenarios and found out that overall performance of CA will most likely decrease in the future in most temperate regions in South 2/24 America, including Uruguay, southern Brazil and northern Argentina for barley, cotton, rice, sorghum and sunflower. Krause et al (2022) has recently modelled the impacts of anthropogenic land cover changes on global Gross Primary Productivity (GPP) using maps of historical agricultural expansion and future land-use changes based on the 25 km resolution LUH2 dataset (Hurtt et al, 2020). Their results indicate that global GPP might get further reduced owing to agricultural expansion and to extents that depend on the prevailing scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that areas currently under forestry are the most productive, followed by areas used today as cropland (Haberl et al., 2007). In high‐productivity tropical forests, land‐cover change usually decreases productivity (Krause et al., 2022), although a transition to a highly productive arable cropland can increase maximum productivity (DeFries et al., 1999; Gosling et al., 2017). However, the average annual productivity of croplands, which includes productivity across the whole cropping cycle, is reduced even though the proportion of the productivity that can be consumed by humans and livestock has increased.…”
Section: Discussionmentioning
confidence: 99%
“…Although partial correlation analysis was applied to eliminate the influence of collinearity of meteorological variables, we did not consider the impact on ecological disturbance on vegetation growth. Ecological disturbances, such as insects (Kurz et al, 2008), fire disturbances (Beck & Goetz, 2011), deforestation (Estoque et al, 2018), land use change (Krause et al, 2022), and human management (Wang et al, 2022), will also greatly affect peak vegetation growth. For instance, over-grazing reduces vegetation greenness (Hilker et al, 2014), and may lead to a spurious negative correlation between peak growth and warming because temperature change in this case is not the main cause for the peak growth.…”
Section: Limitations and Challengesmentioning
confidence: 99%